Aplikasi Buku Pintar Pelajaran Kimia Kelas X Di SMA Negeri 8 Surakarta Berbasis Android Mobile - Bagus Candra W.; Dwi Kuncoro (Sekolah Tinggi Manajemen Informatika dan Komputer AUB - Indonesia, 2017)
Chemistry is the branch of physics which studies the composition, structure, characteristics as well as the alteration of material. There are lots of formulas in Chemistry, this makes many students lose their enthusiasm in learning the subject. They find it difficult to memorize all the formulas. Nowadays, Chemistry becomes an important subject and it has been taught to the students in the tenth grade. SMA Negeri 8 Surakarta is one of the high-schools that had applied the teaching of Chemistry to the tenth grade students. Students think of Chemistry as a difficult subject, because they have to grasp and understand many concepts in a relatively short time. As a result, many students fail in the subject. This research system that was built using the framework of CI to the backend that runs the teacher while the Ionic framework for androidnya who run their students. In SMA Negeri 8 Surakarta, a handy and practical Chemistry Smart Book Application grade X was created to help the students get better understanding about Chemistry that full of formula as well as to help the teacher in delivering and assessing the subject.Keywords: Learning Media, Chemistry Smart Book Application Grade X in Negeri 8 Surakarta, Mobile Android